Analisis Perbandingan Kinerja Keuangan BPR Sebelum dan Sesudah Pengumuman Covid-19 (Studi Kasus pada PT. BPR LPN Talawi Sakato) - Dwi Putria, Welsy; Chandrayanti, Teti; Begawati, Nova (Ekasakti Matua Jurnal Manajemen, 2024)
This study aims to analyze the comparison of BPR financial performance at PT. BPR LPN Talawi Sakato before and after the announcement of Covid-19. By using financial ratios, the study time frame is from Quarters I to IV in 2018 to 2022. The financial ratios used include QR, LDR, ROE, CAR, PR, and BOPO. The data used in this study were obtained from the financial statements of PT. BPR LPN Talawi Sakato 2018-2022. The analysis technique used to see a comparison of the financial performance of PT. BPR LPN Talawi Sakato is the Independent sample t-test method. The results showed that there were significant differences for each of the financial ratios at PT.BPR LPN Talawi Sakato. Significant differences before and after the announcement of Covid-19 were found in the ratios of LDR, PR and CAR.